Domestic Chicken Eggshell-Derived Bone Substitute: Synthesis, Characterization and In Vitro Cell Viability - Sruthy Prathap; K. S. Rajesh; Nebu G. Thomas; Jeyachandran Venkateshan; M. S. Prathap; Suprith Surya (Journal of Pharmacy and Bioallied Sciences)
Background: Hydroxyapatite (HA) is a material with excellent bioactivity and chemical similarity to bone. It can be extracted from natural sources or fabricated synthetic sources. Objective: To synthesize HA from domestic chicken eggshells and to characterize it using Fourier transform infrared (FTIR), X-ray powder diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy, and cell viability. Materials and Methods: Domestic chicken eggshells (Indian breed “Aseel”) were used to synthesize HA through the chemical precipitation method. The processing was conducted at an elevated temperature (900°C). Characterization of the sample was performed using, FTIR, SEM, EDS, and XRD. The cell viability was tested in vitro using methyl thiazolyl tetrazolium assay. Results: Phosphate and calcium ions were confirmed by FTIR and EDS. The carbonate peaks observed were typical of biological apatite. XRD revealed its crystalline property. SEM analysis confirmed the particle size to be less than 100 μm and the presence of a porous structure. The material was found to be noncytotoxic and favored cell growth. Conclusion: The synthesized HA showed a crystalline nature and had good cell viability. Hence, it may be considered as a material for various biomedical applications.